Karakteristik Kimia dan Sensori Brownies Ubi Jalar Putih dengan Penambahan Tepung Kacang Hijau - Rahmah, Annisa L; Ayu, Dewi F; Fitriani, Shanti (Universitas Pattimura, 2024)
Brownies are a kind of cake that is dark brown in color, has a smooth texture and special taste, and does not require baking powder. White sweet potatoes and mung beans can be used as raw material for brownies, where white sweet potatoes have a fairly high carbohydrate content while mung beans have a high protein content. The purpose of this study was to obtain the effect of white sweet potato and mung bean flour on the chemical and sensory characteristics of brownies and to obtain the best ratio. The treatment in the study consisted of five treatments and three replications and used a CDR (Completely Randomized Design). The ratios of white sweet potato and mung bean flour, namely 100:0, 90:10, 80:20, 70:30 and 60:40. The results of the research on the selected treatment were 80% white sweet potato flour : 20% mung bean flour, which had moisture content of 30.44%, ash content of 0.96%, fat content of 20.31%, protein content of 12.42%, carbohydrate content of 35.88%, and fiber content of 6.62%. The descriptive test showed that the brownies had a brown color, mung beans and sweet potato flavor, mung beans and sweet potato taste, and soft texture.